The Analysis of Raw Material Control using the Economic Order of Quantity (EOQ) Method in Teng-teng Mulyati Home Industry - Virginia, Tiara Rahma; Hamdani, Deni (STIE Ekuitas, 2024)
Introduction/Main Objectives: The purpose of this study was to analyze raw material inventory control with Economic Order Quantity (EOQ) method for helping the company to control the inventory of raw material by looking for how much raw material the rice must be ordered so that the company does not experience shortages and advantages in its raw materials, so the inventory in the company is optimal. Finding/Results: The result showed that Economic Order Quantity (EOQ) is the appreciate and can optimize the supply of special vehicle raw material in home industry Teng-teng Mulyati compared with the existing policies in the company, using the Economic Order Quantity (EOQ) method the order quantity becomes 682 kg with 1 time the order frequency, Safety Stock 679,98 kg, Reorder Point 718,61 kg, Maximum Inventory 1.361,98 kg, so the Total Inventory Cost is Rp. 174.539,39. Conclusion: This method can be a company reference in controlling the inventory of raw material and by using this method the company obtains cost savings between calculations based on company policy and the Economic Order Quantity (EOQ) method.